UAN - Fixed sub-surface notes (projects plan) - Zabel, F. (2014)
This document describes requirements for the Fixed Sub-Surface Nodes (FNO) two of which are to be developed for the Underwater Acoustic Network (UAN) project. The fixed nodes serve as sensor platforms which are to be deployed and work autonomously and cable-less on the sea floor. Communication with these nodes is to be acomplished by using underwater acoustic modems. A description of hardware and software is included in this document. Mechanical drawings can be found in the appendix.